Between the Third Rome and the New Jerusalem The Fall of Constantinople Viewed by Russians - Torres Prieto, Susana (Cambridge Scholars Publishing, 2014)
-
Keywords: 55 Historia::5504 Historia por épocas::5504.03 Historia medieval; ODS 11 - Ciudades y comunidades sostenibles